Representative Virtual Material Collections about University Scientists: The Experience of the Uzhhorod National University Library - Medved, M. M. (Ukrainian State University of Science and Technologies, Dnipro, 2023)
ENG: Objective. The research is aimed at studying practical experience of creation and application of the representations of virtual material collections about the scientists of the Uzhhorod National University, as one of the important popularization mechanisms of the university science. Methods. Using our own developments, we attempted to familiarize the library community with the specialized methodology of representation work of the scientific library of the Uzhhorod National University during quarantine restrictions and martial law in Ukraine. Using the comparative analysis, the efficiency of the representations of virtual material collections, created by the library as publicizing the development of university science and culture of the region and the interest of remote users in them has been proven. Results. The substantiation of the obtained results is based on the characteristics of the Uzhhorod National University library during remote work of the institution, aimed at increasing the interest of virtual users in the content of the library. The efficiency of using the method of representations of information products of libraries during the period of difficult physical access to the library funds of Ukraine has been confirmed. Analysis of the expansion of the library’s information services and the practical recommendations regarding the active popularization of scientists and prominent figures of the Zakarpattia region are considered as one of the methods of reorienting the work of the library and its services in accordance with today’s challenges. Conclusions. The important role of library support in the popularization of science and culture of the region, as an important factor of practical library assistance to society during the times of trials for Ukraine, has been confirmed.

UKR: Мета. Дослідження спрямоване на вивчення практичного досвіду створення та застосування репрезентацій віртуальних колекцій матеріалів про вчених Ужгородського національного університету, як одного з вагомих механізмів популяризації науки університету. Методика. За допомогою власних напрацювань здійснена спроба ознайомити бібліотечну спільноту з профільною методикою репрезентаційної роботи наукової бібліотеки Ужгородського національного університету під час карантинних обмежень та воєнного стану в Україні. За допомогою порівняльного аналізу доведено ефективність репрезентацій віртуальних колекцій матеріалів, створених бібліотекою, як оприлюднення розвитку університетської науки та культури краю та зацікавленість ними віддалених користувачів. Результати. Обґрунтування отриманих результатів базується на характеристиці роботи бібліотеки Ужгородського національного університету під час дистанційної роботи установи, спрямованої на підвищення інтересу віртуальних користувачів до контенту книгозбірні. Підтверджено ефективність застосування методу репрезентацій інформаційних продуктів бібліотек за період складнощів фізичного доступу до фондів бібліотек України. Аналіз розширення інформаційних послуг бібліотеки та винесені практичні рекомендації щодо активної популяризації науковців та видатних постатей закарпатського краю розглянуто як один із методів переорієнтування роботи бібліотеки та її послуг відповідно викликам сьогодення. Висновки. Підтверджено важливу роль бібліотечної підтримки в популяризації науки та культури краю як важливого чинника практичної бібліотечної допомоги соціуму в період важких випробувань України.
Репрезентативні віртуальні колекції матеріалів про вчених вишу: досвід бібліотеки Ужгородського національного університету
M. Medved: ORCID 0000-0001-8275-9026
Keywords: Scientific Library of the Uzhhorod National University; library innovations; representations of virtual materials; virtual exhibitions; Наукова бібліотека Ужгородського національного університету; бібліотечні інновації; репрезентації віртуальних матеріалів; віртуальні виставки; SOCIAL SCIENCES::Other social sciences::Library and information science